Alveolar bone loss is associated with oral cancer: a case-control study - Trumet, Leah; Fuchs, Roman; Backhaus, Joy; Grötsch, Bettina; Galler, Kerstin; Kesting, Marco; Weber, Manuel (Frontiers in Oral Health, 2025)
BackgroundA link between chronic inflammation and malignant transformation is evident in various cancer types. Periodontitis is the most common chronic inflammatory condition in oral medicine with a proven association with systemic diseases like diabetes. Although there is scant evidence of a potential link between periodontitis and oral cancer there is no proof for a correlation yet. We hypothesize that radiographic bone loss (RABL) as indicator of chronic periodontitis is associated with the occurrence of oral squamous cell carcinomas (OSCC).Methods206 orthopantomograms (OPTs) from a cohort of OSCC cases and controls without OSCC, both between the age of 40 and 70, were analyzed in this retrospective study. Radiographic oral health parameters like radiographic alveolar bone loss (RABL), remaining teeth as well as implants were analyzed and compared between the two groups. The analyses of the study were controlled for the impact of confounders such as diabetes, smoking of tobacco and age. Welch-test, Chi-Square-Test and a two-way Analysis of Covariance (ANCOVA) followed by a Bonferroni post-hoc test for multiple pairwise comparison were performed.ResultsSeveral statistically significant differences were identified between the two groups, with a greater than twofold prevalence of nicotine consumption among the OSCC group. Additionally, the OSCC cohort exhibited a mean age approximately 3.5 years higher and a lower number of remaining teeth compared to the control group. After eliminating the effect of these confounders, a significantly greater loss of bone mass was observed in the OSCC cohort in comparison to the control cohort.ConclusionIn consideration of the confounders, patients with OSCC had more bone loss, compared to controls. These data indicate an association between periodontitis derived chronical inflammation and the malignant transformation of oral epithelium.